Topics in percolative and disordered systems - Ben Arous, Gerard; Ferrari, Pablo A.; Newman, Charles M.; Sidoravicius, Vladas; Vares, Maria Eulália; Ramirez, Alejandro F. (Springer Proceedings in Mathematics & Statistics, 2014)
This volume features selected and peer-reviewed articles from the Pan-American Advanced Studies Institute (PASI). The chapters are written by international specialists who participated in the conference. Topics include developments based on breakthroughs in the mathematical understanding of phenomena describing systems in highly inhomogeneous and disordered media, including the KPZ universality class (describing the evolution of interfaces in two dimensions), spin glasses, random walks in random environment, and percolative systems. PASI fosters a collaboration between North American and Latin American researchers and students. The conference that inspired this volume took place in January 2012 in both Santiago de Chile and Buenos Aires. Researchers and graduate students will find timely research in probability theory, statistical physics and related disciplines.